1985
DOI: 10.1080/01635588509513823
|View full text |Cite
|
Sign up to set email alerts
|

The role of selected dietary elements in breast cancer risk among native and migrant populations in poland

Abstract: Breast cancer incidence was analyzed for natives of Upper Silesia, Poland, and for migrants to this region, to determine its relationship with the consumption of roasted and boiled meat, fat, salt, and raw vegetables. No significant associations were found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1989
1989
2003
2003

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 22 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…Many case‐control studies in multiple populations around the world have found a positive association between intake of meat,23, 24, 25 red meat,25, 26 high fat meat,27 beef,28, 29 pork,28, 30 sausage24 and animal protein26 and risk of breast cancer. However, no association between total meat consumption and breast cancer risk was seen in one case‐control study based in Poland with 328 cases31 and another in Iowa, U.S. with 273 cases 15. A meta‐analysis of 12 case‐control studies published in 1993 by Boyd et al 32 found a summary RR (95% CI) of 1.14 (1.02–1.29) for the highest compared to the lowest category of meat intake.…”
Section: Discussionmentioning
confidence: 97%
“…Many case‐control studies in multiple populations around the world have found a positive association between intake of meat,23, 24, 25 red meat,25, 26 high fat meat,27 beef,28, 29 pork,28, 30 sausage24 and animal protein26 and risk of breast cancer. However, no association between total meat consumption and breast cancer risk was seen in one case‐control study based in Poland with 328 cases31 and another in Iowa, U.S. with 273 cases 15. A meta‐analysis of 12 case‐control studies published in 1993 by Boyd et al 32 found a summary RR (95% CI) of 1.14 (1.02–1.29) for the highest compared to the lowest category of meat intake.…”
Section: Discussionmentioning
confidence: 97%
“…Several other studies have investigated the association between fiber-rich foods or food groups and risk of breast cancer: a casecontrol study in Singapore 29 showed a significant decrease in risk with intake of soya beans, a good source of both dietary fiber and phyto-estrogens; a case-control study in Moscow 3° showed a strong inverse association with cellulose intake in postmenopausal women; while findings with respect to vegetable intake have been mixed. 21,[25][26][27]38 In conclusion, the results of the present cohort study, in combination with those from several previous studies (both case-control and cohort), provide some evidence for inverse associations between risk of breast cancer and dietary intake of fiber (from cereal sources), and vitamins A (from G-carotene, in particular) and C; previous studies provide some evidence for an inverse association with vitamin E. The associations which have been observed to date generally have been relatively modest, which may reflect the attenuation of risk estimates due to the measurement error which accompanies use of the currently available methods for assessment of dietary intake2 9 As such, the true associations may be stronger, which suggests that if the relationships are shown to be causal, the potential for dietary modification to reduce the risk of breast cancer might be substantial.…”
Section: Discussionmentioning
confidence: 99%
“…Only two other ORs were reported (those for cruciferous vegetables TM and carrotsm), and these were in the inverse direction. Although cruciferous vegetables were the only vegetable subgroup described in Byer's study, 121 a significantly lower risk was seen for higher intake of vitamin A from fruits and vegetables (OR--0.4, P< 0.1, for age group [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49]. (adjusted for age and body mass index), but no association for carrot intake.…”
Section: Ovarian Cancermentioning
confidence: 99%